2001
DOI: 10.1002/jmv.2131
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses against B‐cell epitopes of the hypervariable region 1 of hepatitis C virus in self‐limiting and chronic human hepatitis C followed‐up using consensus peptides

Abstract: A rare collection of serum samples from patients with hepatitis C virus (HCV) infection followed up from the onset of clinical symptoms was acquired. RNA corresponding to the hypervariable region 1 (HVR1) of E2 protein of HCV isolated from nine patients was reverse-transcribed, amplified, sequenced, and HVR1 amino acid sequences were deduced. These sequences and a selection of HVR1 amino acid sequences of matching HCV genotypes from protein and translated DNA sequence databanks were used to create the HVR1 ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The conservation pattern observed in this consensus sequence could be responsible for the observed crossreactivity of human sera to different HVR1 variants Li et al, 2001]. The number of sera reactive with each HVR1 protein correlated significantly with the number of amino acid residues identical to the consensus sequences [Hattori et al, 1998;Watanabe et al, 1999;Isaguliants et al, 2002]. The results of the present study also proved this hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…The conservation pattern observed in this consensus sequence could be responsible for the observed crossreactivity of human sera to different HVR1 variants Li et al, 2001]. The number of sera reactive with each HVR1 protein correlated significantly with the number of amino acid residues identical to the consensus sequences [Hattori et al, 1998;Watanabe et al, 1999;Isaguliants et al, 2002]. The results of the present study also proved this hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…We found that anti-HVR1 antibodies were widely produced in chronic patients, and there was no significant difference in mild hepatitis, moderate hepatitis and liver cirrhosis. That means that the anti-HVR1 antibodies could not be used in prognostic and turnover studies of chronic HCV infection, which was coincided with other studies [14,21] .…”
Section: Discussionsupporting
confidence: 67%
“…Because HCV does not grow robustly in cell culture, it has been difficult to demonstrate Nt Ab to the virus and, thus, to determine whether Ab protects against hepatitis C. The demonstration that both experimentally infected chimpanzees and naturally infected humans could be reinfected with HCV suggested that classical humoral immunity did not develop after resolution of hepatitis C (21-23). However, the demonstration by others that the early development of antibodies to the HCV envelope proteins, and especially to the E2 glycoprotein hypervariable region, correlated with recovery from the infection suggested that such antibodies may play a role in clearance of the virus (24)(25)(26) and that this region of the HCV envelope was under pressure from the humoral immune system. The demonstration that HCV could replicate, albeit not robustly, in certain lymphoid cells of human origin provided a means for testing for Nt Ab, and Shimizu et al (1) demonstrated that serum obtained 2 years after onset of HCV infection in a chronically infected patient could neutralize the homologous virus derived from the acute phase of infection and that serum samples obtained Ͼ5 years after infection could no longer neutralize the acute-phase virus but could neutralize variants that had emerged subsequently.…”
Section: Discussionmentioning
confidence: 99%